Succession planning in SMEs - Abdullah, Moha Asri; Hashim, Junaidah; Hamid, Zarinah; Abd Ghadas, Zuhairah Ariff; Amin, Md. Fouad (IIUM Press, 2012)
The essence of succession planning is crucial to any businesses, big or small, old or new, modern or traditional businesses. This is especially so among small and medium enterprises (SMEs) as they cannot afford to withstand any major setback for continuity and sustainability in, both developing and developed countries alike. Malaysia is not exceptional to this. This simple book focuses on succession planning in family-owned retailing and manufacturing businesses of East Coast Economic Region (ECER) in Malaysia. This book attempts to delineate three succession issues in family businesses i.e., succession dilemma, successor attributes and succession plan. This book argues that to a certain extent, SME owners face some dilemmas while various factors such as business challenges, managerial capabilities, trustworthiness, loyalty, flexibility etc. are related to succession attributes.